1933
DOI: 10.3181/00379727-30-6864
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical Aspects of Sex in Plants.

Abstract: of any movement, absence of mitosis (Slifer') and very low rates of respiratory metabolism (Bodine'). The third period begins with the resumption of mitotic activity followed by blastokinesis. After the embryo has revolved, it grows rapidly and engulfs the remaining yolk. The third phase marks the completion of differentiation and embryonic o rganogenesi s.This preliminary report on the glutathione reaction is based upon observations of 13 embryos in early development, 70 embryos in diapause, and 30 in various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1937
1937
1999
1999

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…Stem length was greater at maturity under long-day than under shortday conditions, a response also noted by MURNEEK (23,29) in soybean and rudbeckia and by WITHROW (40) in a number of other species. Rapid extension of the main axis of the 16-hour plants occurred relatively late in ontogeny as also observed by DANIELSON (11).…”
Section: Discussionsupporting
confidence: 54%
“…Stem length was greater at maturity under long-day than under shortday conditions, a response also noted by MURNEEK (23,29) in soybean and rudbeckia and by WITHROW (40) in a number of other species. Rapid extension of the main axis of the 16-hour plants occurred relatively late in ontogeny as also observed by DANIELSON (11).…”
Section: Discussionsupporting
confidence: 54%
“…This relationship has also been shown to exist in the tops of flowering, plants of Spinacia (14). The imlportance of phospborus in metabolic processes of plants in general suggests specific importanee in relation to sex.…”
Section: Methodsmentioning
confidence: 80%
“…Both of these workers used the entire plant above-ground. LOEHWING (19), however, found that, in the case of spinach, the pistillate plants were slightly more acid than the staminate, and in hemp he found the same. Such variations in the findings might be due to factors in the environment under which the plants were grown, since methods of testing were the same.…”
Section: Discussionmentioning
confidence: 93%
“…In a later work (33) he also found the active acidity of expressed sap of staminate plants to be greater than that of female plants. LOEHWING (19) found that the tops of 15-week-old spinach plants were slightly more acid in the case of the female plants. Likewise in hemp he found that the tops of 10-week-old plants showed a slightly higher pH for the males.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation